How do Brand Experience, Love, dnd Commitment Affect Positive Word of Mouth Among Skincare Users in Samarinda City - Pramesti Wijaya, Alma Argriphi Ardhia; Adhimursandi, Doddy (PT. Hanken SUkses Jaya, 2024)
This study aims to explore and elucidate the impact of brand experience, brand love, and brand commitment on positive word-of-mouth for skincare users in Samarinda City. The study population comprised consumers who purchased skincare products from the Somethinc Offline Store SOGO Big Mall located in Samarinda City, East Kalimantan. The researchers utilized a non-probability sampling technique with purposive sampling to select 120 respondents. Data were collected through questionnaires and analyzed using partial least squares with SmartPLS Application version 4.0. The study's findings imply that Brand Experience exerts a favorable and substantial impact on positive word-of-mouth, while brand love also has a favorable and significant influence on positive word-of-mouth. Additionally, brand commitment is found to have a positive and significant impact on positive word-of-mouth.